Foreign Language Capability as a Strategic Resource for Strengthening MSME Marketing Competitiveness - Yeni Artanti; Lusi Nurhayati; Sudarmaji Sudarmaji; Nur Hidayanto Pancoro Setyo Putro; Shafira Alyssa Difiputri; Syafina Azalia; Ruth Fenandha Pramasita (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Micro, small, and medium enterprises play a central role in fostering inclusive economic growth, yet many continue to face constraints in accessing wider markets. In increasingly globalized and digitalized business environments, limited foreign language capability has emerged as an underexplored barrier that restricts MSME marketing effectiveness and competitiveness. This study aims to examine how foreign language competence, developed through a structured training and mentoring program, contributes to strengthening MSME marketing practices within a community empowerment context. Adopting a qualitative dominant mixed methods design, the study drew data from participating MSME owners across multiple sectors, including interviews, observations, questionnaires, and analysis of marketing materials produced before and after the intervention. The findings reveal that foreign language capability enhanced participants’ confidence, improved the clarity and functionality of marketing communication, and fostered greater strategic awareness in presenting products to broader audiences. Rather than serving merely as a symbolic attribute, foreign language use functioned as an applied strategic resource that supported more professional branding and customer engagement. However, the results also indicate that capability development was gradual and shaped by contextual constraints such as limited time, digital literacy, and concerns over accuracy. The study contributes to literature by positioning language competence as an intangible form of human capital and strategic capability relevant to MSME competitiveness. Practically, the findings suggest that empowerment programs aligned with sustainable development objectives should integrate foreign language training with applied marketing practice and sustained mentoring to achieve meaningful and lasting outcomes.